Lay Up Shoot Technique in Basketball Games - Ishak, Muhammad; Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research aims to determine the relationship between leg explosive power, wrist flexibility, and hand-eye coordination on lay-up shooting ability. This type of research is a type of descriptive research. The research variables consist of independent variables, namely leg explosive power, wrist flexibility, and hand-eye coordination, while the dependent variable is lay-up shooting ability. The population in this study were all BKMF FIK UNM college college students with a research sample of 30 people. The sampling technique is to use "total sampling" meaning that the entire population becomes the sample. The data analysis technique used is correlation and regression analysis using the SPSS Version 22.00 system at a significance level of 95% or (α) = 0.05. Based on the results of data analysis, this research concludes that: 1). There is a relationship between leg explosive power and lay-up shooting ability, as proven by the calculated r-value (ro) = 0.680 (P=0.000 < α:0.05) for an R squared value (coefficient of determination) of 0.462. This means that 46.2% of lay-up shooting ability is explained by leg explosive power; 2). There is a relationship between wrist flexibility and lay-up shooting ability, as proven by the calculated r-value (ro) = 0.734 (P=0.000 < α:0.05) for an R squared value (coefficient of determination) of 0.539. This means that 53.9% of lay-up shooting ability in basketball is explained by wrist flexibility; 3). There is a relationship between hand-eye coordination, wrist flexibility, and lay-up shooting ability, as proven by the calculated r-value (ro) = 0.689 (P=0.000< α:0.05) for an R squared value (coefficient of determination) of 0.474. This means that 47.4% of lay-up shooting ability in basketball is explained by hand-eye coordination; 4). There is a relationship between leg explosive power, wrist flexibility, and hand-eye coordination on lay-up shooting ability, as proven by the calculated r-value (ro) = 0.768 (P=0.000< α:0.05) for an R squared (coefficient of determination) value of 0.590. This means that 59% of lay-up shooting ability in basketball is explained by leg explosive power, wrist flexibility, and eye-hand coordination